2015
DOI: 10.1186/s13098-015-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Social class and metabolic syndrome in populations from Tunisia and Spain

Abstract: BackgroundThere is an increasing prevalence of obesity and metabolic syndrome (MS) in developing countries. It has been shown the relationship between social class and MS in developed countries. The objective of our study was to compare the association of social class with the prevalence of MS in a developing country (Tunisia, region of Cap-Bon) and a developed one (Spain, Canary Islands).MethodsCross-sectional study of 6729 Canarian and 393 Tunisian individuals. Social class was measured with the income, crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…These results confirmed previous findings in Tunisian population [5][6][7]17 as well as in others population [18][19][20][21] . Sedentary lifestyle, the lack of participation in physical activities among adult Tunisian women, hormonal factors and postmenopausal weight gain may prove the large waist circumference in women 22,23 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirmed previous findings in Tunisian population [5][6][7]17 as well as in others population [18][19][20][21] . Sedentary lifestyle, the lack of participation in physical activities among adult Tunisian women, hormonal factors and postmenopausal weight gain may prove the large waist circumference in women 22,23 .…”
Section: Discussionsupporting
confidence: 92%
“…In Tunisia, few studies have focused on the prevalence of MS [5][6][7] . On the other side, the prevalence of obesity is high and is increasing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…women in the present study also showed lower prevalence of MS, which placed them in a situation similar to that encountered in higher income countries 29 .…”
Section: Discussionsupporting
confidence: 82%
“…Recently, in Tunisian population Gannar et al . found that abdominal obesity was significantly more frequent in women than in men, with higher prevalence of MetS in women with 93%.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Obesity is a multifactorial condition influenced by the combined effects of genes and environment and also their interactions. 40 Recently, in Tunisian population Gannar et al 41 found that abdominal obesity was significantly more frequent in women than in men, with higher prevalence of MetS in women with 93%. Although the number of candidate genes has increased and several polymorphisms have been studied in human populations, knowledge about genetic factors underlying the susceptibility to obesity remains incomplete.…”
Section: Discussionmentioning
confidence: 99%